The Effect of Turmeric (Curcuma domestica) Extract on Water Holding Capacity, Cooking Loss, pH Values and Tenderness of Broiler Chicken Meat - Negari, Indira Putri; Isroli, Isroli; Nurwantoro, Nurwantoro (ANIMAL PRODUCTION, 2014)
Abstract.Â  This study was aimed to determine the influences of turmeric extract supplementation on water holding capacity, cooking loss, pH value and tenderness of broiler chicken meat Data analysis was subject to completely randomized design 5 treatments namely T0, T1, T2, T3 and T4 containing non-turmeric extract, 100 mg/kgBW/day, 200 mg/kgBW/day, 300 mg/kgBW/day and 400 mg/kgBW/day, respectively. Each unit of experiment administered 3 heads with four replications. The results indicated no effect from turmeric extract supplementation on water holding capacity, cooking loss, pH value and tenderness of broiler chicken meat. The average treatments of T0, T1, T2, T3, T4 had water holding capacities ofÂ  39.86, 37.58, 36.41, 36.94, respectively; cooking losses of 26.00, 27.58, 27.57, 27.11, and 27.49%, respectively; tenderness of 1.97, 1.95, 1.63, 1.77 and 1.99 Nmm, respectively, and final Body weights of 1,618.5, 1,568, 1,692.5, 1,651.75 and 1,462 g/head, respectively. However, a highly significant influence was observed on the pH values of 6.46, 6.04, 6.21, 6.08 and 5.98. The results indicated that none of the turmeric extract supplementation increased water holding capacity, cooking losses, tenderness and body weight.Â Key words: broiler, cooking loss, pH values, tenderness, water holding capacity, turmericÂ Abstrak. Penelitian ini bertujuan untuk mengetahui pengaruh pemberian ekstrak kunyit terhadap daya ikat air, susut masak, nilai pH dan keempukan daging ayam broiler. Manfaat penelitian yaitu tersedianya informasi ilmiah tentang ekstrak kunyit terhadap danging ayam broiler. Perlakuan yang diterapkan adalah T0 tanpa ekstrak kunyit, T1 100, T2 200, T3 300, dan T4 400 mg/kgBB/hari. Data analisis yang digunakan adalah rancangan acak lengkap yang terdiri dari 5 perlakuan dan 4 replikasi. Setiap unit percobaan terdiri dari 3 ekor. Hasil penelitian menunjukkan tidak ada pengaruh pemberian ekstrak kunyit terhadap daya ikat air, susut masak, dan keempukan daging ayam broiler. Rataan untuk perlakuan T0, T1, T2, T3, T4 pada Daya Ikat Air masingâmasing 39,86; 37,58; 36,41; 36,94; 34,78%; susut masak 26,00; 27,58; 27,57; 27,11; 27,49%, keempukan 1,97; 1,95; 1,63; 1,77; 1,99 Nmm, dan bobot badan akhir 1.618,5; 1.568; 1.692,5; 1.651,75; 1.462g/ekor. Namun, memberikan pengaruh sangat nyata pada nilai pH 6,46; 6,04; 6,21; 6,08; 5,98. Hasil Â menunjukkan bahwa pemberian ekstrak kunyitÂ  tidak meningkatkan daya ikat air, susut masak, keempukan dan bobot badan.Â Kata Kunci : Broiler, Susut Masak, pH, Keempukan, Daya Ikat Air, Kunyit